Pulmonary aspergillosis in a horse: a case report - Melo, Ubiratan Pereira; Ferreira, Cíntia; Barreto, Suziane Wilma Mota (Brazilian Journal of Veterinary Medicine, 2024)
Respiratory diseases considerably affect equine athletes, being the second most common cause of poor performance. Among these diseases, fungal pneumonia in horses, caused specifically by Aspergillus spp., is relatively rare but potentially fatal. Fungal pneumonia typically affects horses exposed to fungal elements due to environmental factors, immunosuppression, or previous debilitating illnesses. Treatment is complex, with minimal success due to late diagnosis and serious concomitant underlying diseases. The choice of medication depends on the site of infection, the fungal species involved, and financial considerations. This report describes a case of pulmonary aspergillosis diagnosed in a 10-year-old castrated Quarter Horse. Transtracheal lavage revealed fungal elements characteristic of Aspergillus fumigatus. Treatment with dexamethasone, bromhexine hydrochloride, and itraconazole led to a successful recovery. The diagnosis of equine aspergillosis is challenging because its clinical signs overlap with other respiratory diseases. Fungal infections like aspergillosis are gaining attention in the equine health scene. Early and accurate diagnosis is crucial to avoid unnecessary use of antibiotics and prevent antimicrobial resistance. Furthermore, veterinarians and horse handlers must be aware of the risks of spreading aspergillosis to humans, emphasizing preventative measures and respiratory protection.